1995
DOI: 10.1016/0014-5793(95)00157-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the DNA‐binding activity of NF‐κB by gold compounds in vitro

Abstract: Nuclear factor loB (NF-IcB) is a transcription factor that is critical for the inducible expression of multiple cellular and viral genes. DNA binding activity is essential for its function. Here, we report that gold compounds, especially aurothioglucose (AuTG), have a strong inhibitory effect on NF-JcB-DNA binding. Our finding also reveals that Zn 2÷ is a necessary component of NF-JcB for its DNA binding activity and that gold ion can efficiently block NF-~,--DNA binding, presumably through oxidation of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 17 publications
2
92
0
Order By: Relevance
“…The inhibitory effect of auranofin appeared by reducing mRNA level of these cytokines, suggesting that it blocks some common step in the signal pathways for the transcriptional activation of IL-1 and TNF genes (30). In conjunction with these results, various metal compounds, including gold thiolates, were shown to inhibit the in vitro binding of NF-B to DNA, albeit only in relatively high concentrations (31).…”
mentioning
confidence: 80%
“…The inhibitory effect of auranofin appeared by reducing mRNA level of these cytokines, suggesting that it blocks some common step in the signal pathways for the transcriptional activation of IL-1 and TNF genes (30). In conjunction with these results, various metal compounds, including gold thiolates, were shown to inhibit the in vitro binding of NF-B to DNA, albeit only in relatively high concentrations (31).…”
mentioning
confidence: 80%
“…Alternatively, under certain circumstances, antioxidants may directly inhibit IKK kinase activity or NF-kB DNA-binding by affecting the redox state of critical Cys residues in the IKK kinase activation loop and NF-kB DNA-binding loop (Gloire et al, 2006;Bubici et al, 2006). For example, the oxidation state of NF-kB seems important for its interaction with DNA (Yang et al, 1995), and its DNA binding can be blocked by interaction with thiol-reactive metals (Shumilla et al, 1998).…”
Section: Antioxidantsmentioning
confidence: 99%
“…On one hand, anti-oxidants could block the production of ROIs that lead to degradation of IkBa. On the other, DNA binding by NF-kB could be directly regulated by the redox potential of the cell; for example, at least in vitro, the oxidation state of NFkB seems important for its interaction with DNA (Yang et al, 1995), and its DNA binding can be blocked by interaction with thiol reactive metals (Shumilla et al, 1998). Animal models have indicated that the anti-oxidant PDTC may have clinical applications for the treatment of septic shock and certain retinal neovascular diseases, due to the ability of PDTC to block NF-kB induction (Lauzurica et al, 1999;Yoshida et al, 1999).…”
Section: Anti-oxidant Moleculesmentioning
confidence: 99%